Perceived need and measured well-being: How well do subjective rankings capture relative poverty? - Ranucci, Immacolata; Abay, Kibrom A.; Tiberti, Luca (International Food Policy Research Institute, 2025)
Subjective well-being rankings are increasingly used to target social protection programs, yet their ability to capture relative welfare and wealth remains debated. This study benchmarks self-, peer-, and elite-based poverty rankings against consumption- and wealth-based measures using Ethiopian household survey data, where about 20 households per village were ranked from neediest to least needy by themselves, peers, and community leaders. We assess concordance between subjective and conventional welfare rankings and explore sources of divergence. Subjective rankings align more with relative wealth than consumption and with total rather than per capita welfare, suggesting they overlook household composition. Elite-based rankings best capture conventional measures, followed by peers’ and self-rankings. Subjective rankings also better reflect relative deprivation among households exposed to covariate shocks. A composite index combining all three improves agreement with standard metrics. Information asymmetries, favoritism, and welfare dynamics partly explain discrepancies, offering insights for enhancing targeting in data-scarce settings.